Multiple pathogens in adult patients admitted with community-acquired pneumonia: a one year prospective study of 346 consecutive patients. Issue 2 (February 1996) - Lieberman, D.; Schlaeffer, F.; Boldur, I.; Lieberman, D.; Horowitz, S.; Friedman, M. G.; Leiononen, M.; Horovitz, O.; Manor, E.; Porath, A.
Abstract : BACKGROUND: The purpose of this study was to assess the causes of community-acquired pneumonia in adult patients admitted to hospital. METHODS: A prospective study was performed on 346 consecutive adult patients (54% men) of mean (SD) 49.3 (19.5) years (range 17-94) admitted to a university affiliated regional hospital in southern Israel with community-acquired pneumonia over a period of one year. Convalescent serum samples were obtained from 308 patients (89%). The aetiological diagnosis for community-acquired pneumonia was based on positive blood cultures and/or significant changes in antibody titres to Streptococcus pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, respiratory viruses, Coxiella burnetii, Mycoplasma pneumoniae, Chlamydia pneumoniae, and Legionella sp. RESULTS: The aetiology of community-acquired pneumonia was identified in 279 patients (80.6%). The distribution of causal agents was as follows: S pneumoniae, 148 patients (42.8%); M pneumoniae, 101 (29.2%); C pneumoniae, 62 (17.9%); Legionella sp, 56 (16.2%); respiratory viruses, 35 (10.1%); C burnetii, 20 (5.8%); H influenzae 19 (5.5%); and other causes, 21 patients (6.0%). In patients above the age of 55 years C pneumoniae was the second most frequent aetiological agent (25.5%). In 133 patients (38.4%) more than one causal agent was found. CONCLUSIONS: The causal agents for community-acquired pneumonia in Israel are different from those described in other parts of the world. In many of the patients more than one causal agent was found. In all these patients treatment should include a macrolide antibiotic, at least in the first stage of their illness.